ANALISIS FAKTOR PENENTU KEPUTUSAN ORANG TUA MEMILIH SEKOLAH ANAK DI SMP MUHAMMADIYAH 4 SURABAYA - Istikhoroh, Siti; Afrizal Miradji, Mohammad; Rahmi, Laili (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study critically examines the determinants of parental decision-making in school choice, emphasizing the roles of service quality and religious value orientation, with school image conceptualized as a mediating construct. A quantitative design, complemented by qualitative interpretation, was employed through structured survey instruments administered to parents, teachers, staff, and students. Empirical findings indicate that service quality does not directly shape parental decisions; its effect is fully transmitted through school image. This underscores the strategic role of institutional reputation as the primary conduit through which service performance translates into parental trust and selection. Conversely, religious value orientation exerts a robust and significant direct influence, underscoring the primacy of ideological and spiritual alignment in educational choice within faith-based contexts. The absence of mediating effects further demonstrates that functional (service-related) and ideological (value-driven) dimensions operate as independent yet complementary determinants. Overall, the study advances theoretical and practical insights into the dual pathways shaping parental choice, highlighting the necessity for schools to balance service excellence with value-based identity in order to remain competitive and trusted within increasingly diverse educational landscapes.